TOKSISITAS AKUT INFUSA KULIT ARI KACANG TANAH (Arachis hypogea L.) PADA MENCIT BALB/ C - Risha Fillah Fithria; Ririn Lispita Wulandari; Devi Nisa Hidayati; Lilis Rejeki (Universitas Wahid Hasyim Semarang, 2018)
ABSTRACTPeanut shell (PS) infusion has been shown to be antithrombocytopenia, but there has been no research on safety standards. This study aims to identify the symptoms of toxic effects, the potency of toxicity and histopathology of liver male Balb/C mice after a single dose of PS infusion. This research uses randomized matched posttest only control group design. Twenty five mice were divided into 5 orally dosage groups, ie, PS infusion with a dose of 0,026; 0.052; 0.104; 0.208 g/20gBW; and negative control of CMC Na 0.5%. The observation period is for 14 days. The results showed that single dose of PS infusion had a pseudo LD50 value ie > 0.208g/20gBW which was practically non toxic. Symptoms to watch out for the BW infusion were passive behavior, bradycnea, hair color change, hair loss, and weight loss at doses of 3 and 4. It is unclear whether liver damage ie inflammation, necrosis, and albuminous degeneration caused by PS infusion or other causes.keywords: acute toxicity, infusion, peanut shell